The Extractive Industry's impact on Economic Growth in SADC Countries - Sime\~ao Nhabinde; Almas Heshmati (Global Labor Organization (GLO), 2020)
The Southern African Development Community (SADC) countries are rich in natural resources and in most of them their extractive industries extract and export natural resources with little industrial processing. This study analyzes the direct and indirect impacts that the extractive industries in the SADC countries have on their economic growth. The study also examines the hypothesis of economic convergence. Its empirical results are based on data from the 11 founding SADC countries covering the period 2004-17. The results show that despite the process of integration, the SADC economies do not converge in terms of per capita incomes. The extractive industries have direct negative impacts on the countries' economic growth thus providing evidence of a resource curse. Extractive industries in South Africa, Botswana, and Namibia have positive direct impacts on their economic growth. However, in terms of indirect impacts, the extractive industries do not have any impact on GDP because their impact on manufacturing, human capital, public expenditure, economic openness, exchange rate, and inflation is insignificant. The study also shows that GDP, the colonial path followed by these countries, and inflation have a negative but insignificant impact on extractive industries, while manufacturing, government expenditure, and economic openness have positive but insignificant impacts in all SADC countries. Human capital and exchange rate are the only factors that have both significant positive and negative impacts on economic growth, respectively.
Keywords: N57; Q13; P48; 330; SADC; Extractive industry; Growth impact; Natural resources; Resource curse; Africa